2018
DOI: 10.1073/pnas.1807658115
|View full text |Cite
|
Sign up to set email alerts
|

The chaperonin TRiC/CCT is essential for the action of bacterial glycosylating protein toxins like Clostridium difficile toxins A and B

Abstract: Various bacterial protein toxins, including toxins A (TcdA) and B (TcdB), attack intracellular target proteins of host cells by glucosylation. After receptor binding and endocytosis, the toxins are translocated into the cytosol, where they modify target proteins (e.g., Rho proteins). Here we report that the activity of translocated glucosylating toxins depends on the chaperonin TRiC/CCT. The chaperonin subunits CCT4/5 directly interact with the toxins and enhance the refolding and restoration of the glucosyltr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 56 publications
1
20
0
Order By: Relevance
“… Rodrigues et al ( 2019 ) Toxins that do not require Hsp90/Hsp70/PPIases GT C. difficile TcdA, TcdB - - - n.a. Haug et al ( 2003a ); Kaiser et al ( 2009 , 2012 ); Dmochewitz et al ( 2011 ); Steinemann et al ( 2018 ) MP B. anthracis lethal toxin - - - n.a. Haug et al ( 2003a ); Zornetta et al ( 2010 ); Dmochewitz et al ( 2011 ) ✔ = folding helper is required for cellular uptake n.a.…”
Section: Discussionmentioning
confidence: 99%
“… Rodrigues et al ( 2019 ) Toxins that do not require Hsp90/Hsp70/PPIases GT C. difficile TcdA, TcdB - - - n.a. Haug et al ( 2003a ); Kaiser et al ( 2009 , 2012 ); Dmochewitz et al ( 2011 ); Steinemann et al ( 2018 ) MP B. anthracis lethal toxin - - - n.a. Haug et al ( 2003a ); Zornetta et al ( 2010 ); Dmochewitz et al ( 2011 ) ✔ = folding helper is required for cellular uptake n.a.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that CCT4/5 directly interacted with the Clostridium difficile toxins A (TcdA) and B (TcdB). Suppression of CCT5 function by compound HSF1A blocked the cytotoxic effects of TcdA and TcdB [ 44 ]. Based on these, we propose that HSF1A may also have a negative impact on FAdV-4 replication.…”
Section: Discussionmentioning
confidence: 99%
“…Most toxins that need chaperones and PPIases for their uptake are ADP-ribosyltransferases including clostridial binary toxins, DT and PT. Toxins such as C. difficile TcdA and TcdB or the Bacillus anthracis lethal toxin which are not ADP-ribosyltransferases are independent of Hsp90, Cyps and FKBPs for their cellular uptake ( Haug et al., 2003a ; Kaiser et al., 2009 ; Zornetta et al., 2010 ; Dmochewitz et al., 2011 ; Kaiser et al., 2012 ; Steinemann et al., 2018 ). Investigation of fusion toxins as well as artificial transport of isolated enzyme subunits further supported this hypothesis.…”
Section: Common Characteristics Of Chaperone/ppiase-dependent Toxins ...mentioning
confidence: 99%